A brief review on anterior urethral strictures - Cheng, Li (Asian J Urol, 2018)
The treatment of urethral strictures remains a challenging field in urology even though there are a variety of procedures to treat it at present, as no one approach is superior over another. This paper reviewed the surgical options for the management of different sites and types of anterior urethral stricture, providing a brief discussion of the controversies regarding this issue and suggesting possible future advancements. Among the existing procedures, simple dilation and direct vision internal urethrotomy are more commonly used for short urethral strictures ( <1 cm, soft and no previous intervention). Currently, urethroplasty using buccal mucosa or penile skin is the most widely adopted clinical techniques and have proved successful. Nonetheless, complications such as donor site morbidity remain problem. Tissue engineering techniques are considered as a promising solution for urethral reconstruction, but require further investigation, as does stem cell therapy.